Effect of Low Solid/Liquid Ratio on Hydrothermal Synthesis of Hydroxyapatite with Green Template from Banana Flower (Musa acuminata Cavendish) - Ferli Septi Irwansyah; Alfi Ikhlasul Amal; Eko Prabowo Hadisantoso; Atiek Rostika Noviyanti; Diana Rakhmawaty Eddy; Azman Bin Ma'Amor; Risdiana Risdiana (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Hydroxyapatite (HA) was successfully synthesized using the hydrothermal method. This study aimed to analyze the effect of a low solid/liquid ratio on the properties of HA crystals. HA synthesis was performed using chicken eggshells and the hydrothermal method at a temperature of 150°C. The solvent amount was kept constant, while the solid amount varied (half-reaction). The characteristics of HA were determined using XRD, FTIR, PSA, and SEM. The results showed that the purity and size of HA were influenced by a low solid/liquid ratio, while the crystallinity remained relatively unchanged, directly impacting the lattice parameter value. FTIR analysis revealed the absence of the O-H group in the sample with the low solid/liquid ratio. PSA results showed a smaller particle size of 0.995 µm for the sample with the low solid/liquid ratio. SEM results demonstrated a smaller particle size in the sample with a low solid/liquid ratio when observed at the same magnification